The trade balance effects of infrastructure services regulation (2013)
This paper addresses the relationship between the design of incentives to firms under regulation, mainly the rule for adjusting tariffs, and trade balance performance of the country. We also explore whether this relationship is relevant or not for a typical developing economy like Argentina. We find it is. To study these issues we perform comparative static numerical exercises using a CGE model where service obligation and no entry in regulated industries are assumed. We show that the capital account openness and the rate of exchange regime could be key elements to match with the regulatory regime. The potential inconsistency between the international trade regime and the regulatory regime should not be rejected a priori. Copyright Springer-Verlag 2013